An experimental and numerical study of droplet motion and enhanced condensation due to mechanical vibrations - Huber, Ryan Andrew (Kansas State University, 2021)
The Energy-Water nexus is devoted to studying how to reduce the amount of water consumption needed to produce power. In 2010, the U.S. energy production accounted for 40% of freshwater withdrawals and 3% of freshwater consumption [1]. This research focuses on reducing the amount of drift loss from evaporative cooling towers at power plants by condensing the drift loss while it is inside the cooling tower, so it may be collected and reused or recycled in the area. Ghosh et al. [2] used a simple mesh screen in order to collect 40% of the drift loss. This research studies the impacts of vibrations on droplet shedding during condensation; the sooner droplets depart from the condensing surface, the higher the rate of heat transfer [3, 4]. This research focuses on understanding the fundamentals of the droplets motion on a vertical hydrophobic surface in order to determine how to best utilize vibrational forces in order to shed the droplets as fast as possible. Visualization studies examined the droplet modes of 3-μL water droplets at three different vibration settings (i.e., 30 Hz, 70 Hz, and 100 Hz). The resulting modes that were observed were rocking (i.e., no droplet slip), ratchet (i.e., droplet slipping), and ejection (i.e., detaching from the surface). In addition to filtered and de-ionized (DI) water, three other water samples (e.g., simulated salt, flue gas desulfurization, and cooling tower blowdown) were tested in this manner in order to determine how the water properties affected the droplet modes. Numerical studies using the lattice Boltzmann method were validated against experimental results. Numerical studies of the de-ionized water droplets allowed for uncoupling of the vibrational directions, showing that vibrational forces in the direction of gravity played the most important role in droplet shedding. The numerical studies also allowed for test cases that were difficult to accomplish with the experimental apparatus to be conducted. Visual condensation tests showed that the vibrations allowed for droplets to begin shedding earlier (i.e., 20 minutes on vibrating compared to 110 minutes on stationary surfaces) and at smaller diameters (e.g., 1 mm vs 5 mm). Experiments were conducted in an environmental chamber at 40 °C and 60% RH. Inside this chamber, condensation heat transfer experiments were conducted on stationary and vibrating hydrophobic surfaces. The condensation heat transfer coefficients of moist air measured in these experiments ranged from 100 to 150 W/m²K, with the average stationary heat transfer coefficient of 120 W/m²K and the average vibrating heat transfer coefficient of 130 W/m²K. Although the measured difference is modest, it shows that there is a possibility of this being a viable method to enhance condensation heat transfer. Further work is needed to improve the condensation rate of the apparatus in order to better understand the impacts and improvements vibrations have on the heat transfer coefficient.
Keywords: Condensation; Vibrations; Droplet motion; Heat transfer; Simulations; Lattice Boltzmann methods